Specific telomerase RNA residues distant from the template are essential for telomerase function - Roy, Jagoree (Cold Spring Harbor Laboratory Press, 1998)
The reverse transcriptase telomerase is a ribonucleoprotein complex that adds telomeric repeats to chromosome ends, using a sequence within its endogenous RNA component as a template. Although templating domains of telomerase RNA have been studied in detail, little is known about the roles of the remaining residues, particularly in yeast. We examined the functions of nontemplate telomerase residues in the telomerase RNA of budding yeast Kluyveromyces lactis. Although approximately half of the RNA residues were dispensable for function, four specific regions were essential for telomerase action in vivo. We analyzed the effects of mutating these regions on in vivo function, in vitro telomerase activity, and telomerase RNP assembly. Deletion of two regions resulted in synthesis of stable RNAs that appeared unable to assemble into a stable RNP. Mutating a region near the 5′ end of the RNA allowed RNP assembly but abolished enzymatic activity. Mutations in another specific small region of the RNA led to an inactive telomerase RNP with an altered RNA conformation.